2009
DOI: 10.3748/wjg.15.5211
|View full text |Cite
|
Sign up to set email alerts
|

Effect of electro-acupuncture on substance P, its receptorand corticotropin-releasing hormone in rats with irritablebowel syndrome

Abstract: EA at ST25 and ST37 can decrease the number of mucosal MC and down-regulate the expression of CRH in hypothalamus, and the expression of SP and SPR in colon of rats with IBS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(45 citation statements)
references
References 33 publications
2
39
0
4
Order By: Relevance
“…Although EA was shown to reduce CRF expression at the hypothalamus in a rat IBS model [43], the mechanism of the inhibitory effect of EA on CRF expression remains unknown. A recent clinical trial demonstrated that acupuncture is effective for treating the patients with posttraumatic stress disorders (PTSD) [44].…”
Section: Discussionmentioning
confidence: 99%
“…Although EA was shown to reduce CRF expression at the hypothalamus in a rat IBS model [43], the mechanism of the inhibitory effect of EA on CRF expression remains unknown. A recent clinical trial demonstrated that acupuncture is effective for treating the patients with posttraumatic stress disorders (PTSD) [44].…”
Section: Discussionmentioning
confidence: 99%
“…29 The same method of EA also was reported to reduce the number of mucosal mast cells in the colon and the expressions of corticotropin-releasing hormone in the hypothalamus and substance P and substance P receptors in the colon of rats with irritable bowel syndrome. 30 In our own laboratory, in rats with visceral hypersensitivity established by colorectal injection of acetic acid during the neonatal stage, EA at ST36 reduced visceral hyperalgesia and reversed the enhanced excitability of colon dorsal root ganglion neurons. 31 Fig.…”
Section: Electroacupuncture and Visceral Hypersensitivitymentioning
confidence: 99%
“…VIP has some actions in the intestine including relaxation of intestinal smooth muscle, sphincters, dilation of peripheral blood vessels, and inhibition of gastric acid secretion . SP is a signaling molecule connecting the nervous system to the immune system, containing the neural pathway that plays an important role in the regulation of gastrointestinal function (Ma et al, 2009). In this study, IL-1, IL-6, IFN-␥ and TNF-␣ levels in periphery, TNF-␣ and TGF-␤ positive cells in small intestine were taken as immune modulation parameters, VIP, SP and gastrin as neuroendocrine regulation parameters, and reserpine treated rats as the animal model of TCM spleen deficiency, to explore the mechanism of Lizhong Pill for reinforcing spleen deficiency from the view of neuroendocrinoimmune regulation.…”
Section: Introductionmentioning
confidence: 99%